هۆشیارى خوێندکارانى زانکۆ سەبارەت بە ڕووداوە مێژووییەکان ڕێکەوتننامەى (سایکس - پیکۆ) وەک نمونەیەک توێژینەوەیەکى مەیدانییە لەزانکۆى سلیمانیدا ئەنجامدراوە - كوردستان (Sulaimani Journal for Humanities, 2018)
ABSTRACT The lives of young adults have always been connected to a history which has witnessed a series of events and agreements. Even though they had not participated in all these affairs, some of the situations had an effect on the future of these individuals in the community. That's why it has always been important for human consciousness to recognize the historical events and situations it has gone through. For this reason, the researcher in this research aims to give significance and concentration on, "Undergraduate student's consciousness towards historical events, for example the Sykes-Pico agreement". Undergraduate students are the definition of the young adults of this community, who are the source of ability and power for the society; moreover, they are also the ones leading towards growth and development in the region. So, we took (228) of these undergraduate students to participate in this research. From what we concluded in the research, we realize that, in general, the students have consciousness towards the historical events, especially the Sykes-Pico agreement. However, this consciousness is not sufficient enough. As a result, this research has prepared some recommendation and suggestions to be considered.